Oral myiasis in a patient with neuropsychiatric impairment: case report - Gonçalves, Rafael Mício Santos; Pereira, Lorran de Andrade; Silva, Albert da Paixão; Melo, Isabelle de Argolo; Barbosa, Diego Maia de Oliveira; Meireles, Daniel Galvão Nogueira (Seven Editora, 2023)
Myiasis is a common zoodermatose in individuals living in rural areas, tropical and subtropical regions, mainly in underdeveloped or developing countries. This paper aims to report a case of myiasis involving the oral cavity, in a patient with neurological deficit, presenting bilateral anterior dislocation of the mandible, as well as to demonstrate the clinical and surgical management and characteristics pertinent to this treatment. A 34-year-old male patient, melanodermic, with neuropsychiatric impairment, attended the Hospital Geral do Estado, in Salvador (Bahia), brought by his companion with a bilateral mandibular dislocation. The intraoral examination revealed partial edentulism in both arches, poor oral hygiene and massive presence of larvae in the maxilla and mandible. After clinical evaluation and complementary imaging tests, with the patient under general anesthesia and nasotracheal intubation, a compress soaked in sulfuric ether was applied to the affected sites, the larvae were mechanically removed, the wound was debrided and inspected, and the edges were reapproximated. The mandibular dislocation was reduced and immobilized with a Barton-type bandage. The patient was given Ivermectin 12mg and antibiotic therapy with Cephalothin 01g, and a new dose of Ivermectin 06mg was used two days after the procedure. After 04 days of hospitalization, the patient presented a good aspect of the wound, laboratory tests without significant changes and clinical and physiological conditions for hospital discharge. Thus, although there is no protocol treatment, the mechanical removal and debridement with the administration of anthelmintics proved effective for the treatment of this condition. DOI: https://doi.org/10.56238/colleinternhealthscienv1-079